Molecular Basis of Fracture Pseudarthrosis Associated with Neurofibromatosis Type 1 - Aysha Khalid, PhD; Nandina Paria, PhD; Jonathan J. Rios, PhD (Journal of the Pediatric Orthopaedic Society of North America)
Neurofibromatosis Type 1 (NF1) is a tumor-predisposition syndrome caused by heterozygous mutations in the NF1 gene. In addition to oncologic manifestations, individuals with NF1 face a heightened risk of developing secondary skeletal complications associated with somatic loss-of-heterozygosity. Long bone dysplasia and post-fracture pseudarthrosis are among the earliest skeletal manifestations observed in children with NF1. Most commonly occurring in the tibia, pseudarthroses are often treated with a combination of resection, fixation, bone grafting, and rhBMP2. Although rates of initial union are reported to be high, the risk of re-fracture and subsequent pseudarthrosis is similarly elevated, and some patients may ultimately require amputation. Basic science research related to NF1 pseudarthrosis is uncovering the cellular pathogenesis of the disease and unlocking new potential treatment paradigms. Here, we review the current understanding of the biological etiology of NF1 pseudarthrosis, informed by molecular studies of patient-derived tissue samples and mechanistic studies utilizing pre-clinical mouse models. Results from these studies are presented within the context of contemporary treatment paradigms. Finally, we introduce novel treatment paradigms currently under investigation in pre-clinical models and discuss how these may potentially translate to improve surgical outcomes in children with NF1 pseudarthrosis. Key Concepts: (1) Fracture pseudarthrosis in patients with NF1 is caused by somatic mutations in the NF1 gene. (2) Somatic NF1 gene mutations hyperactivate the MAPK signaling pathway, disrupting cellular mechanisms necessary for proper fracture healing. (3) Emerging therapies aim to target hyperactive MAPK signaling to promote fracture healing by fostering osteogenic instead of fibrogenic pathways in skeletal progenitor cells.